Pengaruh Future Time Perspective, Career Adaptability Dan Literasi Digital Terhadap Kesiapan Kerja Mahasiswa Semester Akhir Di Kota Semarang - Widiawati, Natasya; Violinda, Qristin; Ratri Nastiti, Prianka (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2025)
This study aims to analyze the impact of future time perspective, career adaptability, and digital literacy on work readiness among final-year students in Semarang. This research uses a quantitative approach with regression analysis. The population of this study consists of 96 final-year students in Semarang. The sampling technique employed is random sampling. The results of this study indicate that: Future Time Perspective has a positive significant effect on work readiness, Career Adaptability has a positive significant effect on work readiness, and Digital Literacy has a positive significant effect on work readiness. In conclusion, readiness to enter the workforce depends not only on technical skills but also on the ability to plan and view the future, adapt quickly to changes in the professional world, and master digital literacy to leverage emerging technologies